ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN DISFUNGSI EREKSI PADA PASIEN BENIGN PROSTAT HIPERPLASIA DI RS YUKUM MEDICAL CENTRE - Kamalia, Avissa Medina; Hadibrata, Exsa; Susianti, Susianti; Sutyarso, Sutyarso (Medula, 2024)
Benign Prostate Hyperplasia (BPH) is the second most common urology’s disease in Indonesia. This disease occurs due to hyperplasia of stromal cells and epithelial cells of the prostate. The clinical manifestations of this disease consist of obstruction symptoms, irritation symptoms, and post void symptoms. People with BPH often complain about the decrease of their quality of life. One of the factor that Impaired to their quality of life is erectile dysfunction. This study aims to identify the factors that impact the incidence of erectile dysfunction in BPH patients at Yukum Medical Centre Hospital. There were 67 men with bph was obtained from Yukum Medical Centre Hospital in January-September 2021. Data were collected with International Index of Erectile Function-5 questionnaire and medical records. Data were analysis with chi-square test using SPSS and a p-value (<0,05 was considered significant). The result showed that 39 BPH patients had erectile dysfunction. Mean age of BPH patiens with erectile dysfunction was 66,74 (SD±6,51) and mean IIEF-5 scores of the BPH patients was 19,41 (SD±4,23). Age and prostate volume had significant impact with p-value 0,004 and 0,002 respectively. Treatment and medication didn’t have significant impact with p-value 0,193, and 0,856 respectively. Age and prostate volume have a significant impact on the incidence of erectile dysfunction in BPH patients. However, treatment and the type of medication doesn’t impact the risk of incident erectile dysfunction in BPH patients.